Human cytomegalovirus-specific CD4 + and CD8 + T cell responses in primary infection of the immunocompetent and the immunocompromised host - Lilleri, Daniele; Zelini, Paola; Fornara, Chiara; Comolli, Giuditta; Revello, Maria Grazia; Gerna, Giuseppe (Clinical immunology (Orlando, Fla.), 2009)
The kinetics of primary human cytomegalovirus (HCMV) infection and specific T-cell responses were investigated in 16 immunocompetent pregnant women and 8 solid-organ transplant recipients (SOTR). T-cell responses to whole HCMV and to pp65 and IE-1 peptides were determined by flow cytometry evaluation of IFNγ production. HCMV-specific CD4 + and CD8 + T-cells appeared earlier and simultaneously in immunocompetent subjects, whereas specific CD8 + T-cells preceded CD4 + T-cells in half of the SOTR examined. The magnitude of the HCMV-specific T-cell pool was comparable. HCMV load reached peak levels 100–1000 times higher in SOTR than in immunocompetent women, while the virus persisted for months in blood of both groups. T-cells directed to pp65 and IE-1 were only detected in a portion of subjects developing a full T-cell response to the whole virus. Thus, the development of cell-mediated immune response in primary HCMV infection may be missed when looking at pp65 and IE-1 peptide-stimulated T-cells only.